Estimation of Total Carbohydrate Content in Some Wild Edible Plants of Kangchup Chingkhong, Senapati District, Manipur, North East India - Singh, O. Noyon; Niranjan, Ch.; Kikim, A. (International Journal of Economic Plants, 2025)
This study was conducted from March to December, 2024 at the laboratory of the Institutional Biotech Hub, Lilong Haoreibi College, Thoubal, Manipur, aimed to estimate the total carbohydrate content of selected wild edible plants (WEPs) collected from the Kangchup Chingkhong area of Senapati District, Manipur. In this study, 32 plant parts from 21 species including trees, shrubs, herbs, and creepers were analyzed using the anthrone method for carbohydrate estimation. The results revealed substantial variation in carbohydrate content across different plant types and organs. Among trees, Wendlandia grandis flowers had the highest carbohydrate concentration (25.59±0.27 mg g⁻¹ dry weight), followed by Acacia pennata leaves (21.28±1.98 mg g-1) among shrubs. High carbohydrate levels were also observed in Alpinia officinarum leaves (17.40±0.93 mg g¹) and Paederia foetida leaves (16.74±0.45 mg g-1), representing herbs and creepers, respectively. These findings highlighted the nutritional potential of WEPs and supported their inclusion in food-based strategies for enhancing dietary diversity and food security. The study advocated for the preservation of ethnobotanical knowledge and recommends further research on seasonal variability, nutrient bioavailability, and other macronutrients to maximize the benefits of these underutilized resources.